PENATALAKSANAAN HOLISTIK PENYAKIT CAMPAK PADA BALITA USIA 3 TAHUN DENGAN RIWAYAT BELUM IMUNISASI CAMPAK DAN TINGKAT PENGETAHUAN KELUARGA MINIMAL MELALUI PENDEKATAN KEDOKTERAN KELUARGA DI WILAYAH KERJA PUSKESMAS SUKARAJA - Umroh, Afidatul; Mayasari, Diana (Medula, 2024)
Measles is a highly contagious disease. Measles is an important cause of child death worldwide. Groups of children of pre-school age and elementary school age are vulnerable to contracting measles because they have weak immune systems. Measles can cause immune amnesia which will affect the immune system, making sufferers susceptible to other diseases or complications. This indicates that holistic and comprehensive patient care is an important matter through the role of the family doctor. The purpose of writing this article is to identify internal, external risk factors and clinical problems found in patients, apply a holistic and comprehensive family doctor approach according to the problems found in patients, and carry out evidence-based medicine management that is family-approach, patient-centered and community oriented. The study is a case report. Primary data were obtained through history taking, physical examination and home visits. The assessment is based on a holistic diagnosis from the beginning, process and end by means of in-depth interviews, observations and patient filling sheets. Patient An. H, 3 years old, has had a continuous fever since 6 days ago, accompanied by a cold cough. On the fourth day of fever, reddish spots appear, starting behind the ears and then spreading to the face, neck, chest, stomach and arms, accompanied by red and watery conjunctiva of the eyes. Neighbor's children experienced the same complaint. The patient has not received measles immunization.